2014
DOI: 10.1016/j.jinorgbio.2014.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Dilution of dipolar interactions in a spin-labeled, multimeric metalloenzyme for DEER studies

Abstract: The metallo-β-lactamases (MβLs), which require one or two Zn(II) ions in their active sites for activity, hydrolyze the amide bond in β-lactam-containing antibiotics, and render the antibiotics inactive. All known MβLs contain a mobile element near their active sites, and these mobile elements have been implicated in the catalytic mechanisms of these enzymes. However little is known about the dynamics of these elements. In this study, we prepared a site-specific, double spin-labeled analog of homotetrameric Mβ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 44 publications
(56 reference statements)
0
14
0
Order By: Relevance
“…The steady-state kinetic constants are similar to those previously reported for wild-type L1 ( k cat = 25 ± 1 s −1 ; K m = 2.9 ± 0.1 μM). 25 Stopped-flow kinetic studies were conducted on the reaction of 40 μM ZnCo-L1 and 40 μM chromacef (Figure 2). The substrate decayed quickly over the first 100 ms of the reaction, and the concentration of the ring-opened, anionic intermediate maximized during the first 20 ms of the reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The steady-state kinetic constants are similar to those previously reported for wild-type L1 ( k cat = 25 ± 1 s −1 ; K m = 2.9 ± 0.1 μM). 25 Stopped-flow kinetic studies were conducted on the reaction of 40 μM ZnCo-L1 and 40 μM chromacef (Figure 2). The substrate decayed quickly over the first 100 ms of the reaction, and the concentration of the ring-opened, anionic intermediate maximized during the first 20 ms of the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The syringes, mixer, and tubing were all contained in a watertight bath that was maintained at 2 °C. 25, 33 Immediately prior to sample collection, the nozzle (and, for the shortest reaction times, the attached mixer) was removed from the bath and held 5 mm above the surface of 2-methylbutane contained in a collecting funnel and maintained at −130 °C by a surrounding bath (Update Instruments) of liquid nitrogen cooled 2-methylbutane. Samples were packed into home-designed EXAFS sample holders at −130 °C; excess 2-methylbutane was decanted, and samples were stored in liquid nitrogen until data collection.…”
Section: Methodsmentioning
confidence: 99%
“…The use of two frequencies deserves comment. As pointed out earlier [42], the same information is available at both frequencies provided that the relaxation rates allow for reasonable dipolar evolution times. Q-band DEER is a much more efficient technique in terms of time and material [46, 47], and was used whenever possible.…”
Section: Methodsmentioning
confidence: 99%
“…Unbound spin label was subsequently removed by size exclusion chromatography on a Sephacryl S-200 column (1.5 cm X 40 cm of bed volume 60 ml). The efficiency of the spin labeling was estimated from the intensity of the cw-EPR signal at 25 °C, as described elsewhere [42]. …”
Section: Methodsmentioning
confidence: 99%
“…[11] Deletion of the entire hairpin loop or mutations on the loop resulted in significantly lower activities of MBLs CcrA, IMP-1, and BcII. [12-15] Previous studies also suggested that this loop is dynamic during catalysis;[12, 13] however, it is not clear how the loop moves during catalysis.…”
Section: Introductionmentioning
confidence: 99%